Sharia Venture Capital As Alternative Capital For MSMEs In Indonesia - Asyari Hasan; Mia Nurkholifah; Raihan Mujadid; Fadli Agustian (Institut Agama Islam Negeri Padngsidimpuan, 2021)
Abstract This study aims to find out how the role or exsitence of Sharia venture capital as an alternative financial institution that provides capital assistance for MSMEs actors in Indonesia. This research is a type of research using qualitative methods with information and data collection techniques through library research and secondary data sources. The results show that the existence of the role of Sharia venture capital as an alternative capital for MSMEs has succeeded in helping MSMEs not only in terms of strengthening capital but also in terms of HR management, with management assistance, increasing product distribution efficiency by utilizing marketing technology and increasing the ability to earn profits. So that the existence of Sharia venture capital becomes an alternative financing for MSMEs in Indonesia. The benefits obtained by MSMEs from sharia venture capital financing are supported by the role of sharia venture capital companies, which of course cannot be obtained from banking institutions.